Patients with musculoskeletal conditions and comorbidities and their expectations towards physiotherapists - Anna Bernhardt Lyhnebeck; John Sahl Andersen; Søren T. Skou; Mette Bech Risør; Ann Dorrit Guassora (Journal of Multimorbidity and Comorbidity)
Background Understanding patients’ expectations of health care is central to providing patient-centered care and improving patient satisfaction. However, the current literature is primarily focused on single disease-specific patient expectations. Aim To develop an in-depth understanding of the expectations patients with musculoskeletal conditions and comorbidities have towards physiotherapists working in private physiotherapy practice. Methods 35 observations with patients with musculoskeletal conditions and comorbidities receiving treatment in a Danish private physiotherapy setting were conducted. Of these, nine patients participated in interviews. A Grounded Theory analysis was undertaken, and categories were formed and agreed upon through an inductive approach grounded in the data. Results Three major themes emerged from the data 1) Professional expertise is needed but will not be enough if enthusiasm fades in a long treatment course 2) Being able to laugh about life when you have many health problems 3) The balance of involvement and the sharing of power and responsibility. Patients express a desire for a strong bond with their physiotherapists, fostering intimacy and mutual understanding. They seek light-hearted interactions and wish to share personal aspects like family dynamics and hobbies. The study also underscores their expectations for sharing power and care tailored to their specific needs. Conclusion Our findings reveal that patients with musculoskeletal conditions and comorbidities have clear expectations of treatment and collaboration with their physiotherapists in private physiotherapy practice. Underscoring personal relationships over physical results and demonstrating that this patient group has resources to support treatment and is clear about levels of involvement and collaboration.